Engaging fathers to support child nutrition increases frequency of children’s animal source food consumption in Rwanda - Flax, Valerie L.; Ouma, Emily A.; Schreiner, M.-A.; Ufitinema, A.; Niyonzima, E.; Colverson, Kathleen E.; Galiè, Alessandra (2023)
Although social support from fathers is associated with improved child feeding practices, evidence on feasible, acceptable, and effective ways to involve fathers in supporting child nutrition, including animal source food (ASF) consumption, is limited. This study was a fol low-on to a trial that tested the effects of social and behavior change communication (SBCC) targeted mainly at mothers to promote ASF consumption by children in households that received an exotic or crossbred cow through the government of Rwanda’s Girinka “One Cow Per Poor Family” program (NCT0345567). A delayed SBCC intervention was provided to mothers in the non-intervention arms prior to the present pre/post study, which targeted fathers in households across the trial study arms. Baseline and endline surveys with a cohort of 149 fathers with a child clear actions they could take to support their children’s ASF consumption. This study shows that an SBCC intervention for fathers can improve children’s ASF consumption and increase fathers’ knowledge, awareness, and support for children’s nutrition.